Sick Day Management for Adults with Diabetes Who Take Insulin - Nancy J. Gal; Linda B. Bobroff (EDIS)
When people have type 1 diabetes or type 2 diabetes and take multiple daily insulin injections, getting a cold or another minor illness can cause their blood glucose levels to go very high. This can result in serious health problems. The best way for people with diabetes to prevent a minor illness from becoming a major illness is to have a personalized sick day plan designed with their health care provider before they get ill. This 3-page fact sheet was written by Nancy J. Gal and Linda B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences, March 2012.